PENERAPAN TEKNOLOGI AUGMENTED REALITY TENTANG ANATOMI TUBUH MENGGUNAKAN METODE MARKER BASED TRACKING UNTUK SISWA KELAS VII SMP/MTS - Tahta Febri P, Gilar; Lusiana, Veronica (Information Technology and Telematics, 2018)
ABSTRACT Augmented Reality is the incorporation of real and virtual objects in the real environment that run effectively in real time. This merger is possible with appropriate technology, interactive which through certain input devices and its integration requires effective tracking. By utilizing AR technology that uses marker based tracking method, it is a method that raises objects with tracking markers that have been converted, creating an Arnatomy which is an application about the anatomy of the human body. This study implements the information obtained in the form of an application which of course can be used as learning and recognition of body organs to junior high school students.